2014
DOI: 10.1111/1346-8138.12577
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of luliconazole cream 1% for dermatophytoses: A Meta‐analysis

Abstract: We evaluated the efficacy and safety of luliconazole cream 1% in the treatment of dermatophytoses. According to our meta-analysis, short-term treatment of luliconazole cream 1% can result in the complete clearance of dermatophytoses. It showed that 1% luliconazole was more effective than controlled drugs or vehicle (week 4: odds ratio = 1.46, 95% confidence interval = 1.12-1.91), and no more adverse events occurred in the 1% luliconazole group (week 4: odds ratio = 1.01, 95% confidence interval = 0.71-1.44). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Heterogeneity of results between each trial was tested using the chi square test ( p > .1, I 2 < 50%). Meta‐analysis was performed in the fixed effect model if no heterogeneity was found between subgroups, otherwise the randomized effect model was used, and comparison of the effects between two groups was expressed by OR and its 95%CI (Feng et al, ; Light & Pillemer, ).…”
Section: Methodsmentioning
confidence: 99%
“…Heterogeneity of results between each trial was tested using the chi square test ( p > .1, I 2 < 50%). Meta‐analysis was performed in the fixed effect model if no heterogeneity was found between subgroups, otherwise the randomized effect model was used, and comparison of the effects between two groups was expressed by OR and its 95%CI (Feng et al, ; Light & Pillemer, ).…”
Section: Methodsmentioning
confidence: 99%
“…For luliconazole, one meta‐analysis 105 on the usefulness of the drug for dermatophytosis (including tinea pedis), one descriptive study 106 and one placebo‐controlled RCT 107 for tinea corporis were reported. Luliconazole 1% cream ( n = 165) once daily for 7 days was shown to be more effective than placebo ( n = 91) in the treatment of tinea cruris ( n = 256).…”
Section: Cq8: Is a Topical Antifungal Agent Recommended For Tinea Corporis/cruris Treatment?mentioning
confidence: 99%
“…Although terbinafine is the gold standard for the treatment of dermatophytosis, new topical drugs have been developed and recently approved by the FDA (Food and Drug Administration) (Gupta and Simpson, 2012). Among them, luliconazole (Feng et al, 2014), efinaconazole (Tosti, 2013), and tavaborole (Zane et al, 2015), proved to be safe and effective (Zeichner, 2015). Topical therapy is usually non-toxic, since systemic absorption tends to be minimal, which eliminates the possibility of drug interactions (Gupta et al, 2017).…”
Section: Introductionmentioning
confidence: 99%